Les mystérieuses antiquités de Prosper Biardot (1805–1873) - Angélique Allaire (Les Cahiers de l'École du Louvre)
Somewhere between an antiquarian keen on Neapolitan archaeology and an impostor, Prosper Biardot cut a paradoxical figure in many ways: his collection comprised particularly interesting terracottas from Magna Graecia and, for some of them, one of the first hypogea excavated in Canosa, Puglia, known as Lagrasta I. He made a not terribly flattering reputation for himself in French archaeological circles because of his inconsistent purchases in the domain of gold- and silverwork and his ideas, which found an echo abroad, particularly in Germany, and especially Switzerland in the thinking of philologist Johann Jakob Bachofen. His publications contain contrasting ideas fluctuating between very innovative positions on restorations and now outdated theories on the symbolism of the terracottas, which were part of the trends of the times. His album of chromolithographic plates is, on the other hand, one of the rare illustrated accounts of this type of work and for this reason regularly cited in the historiography of the discipline. It is the career and the identity of this ambiguous personally of nineteenth-century collecting, the contemporary of Marquis Campana, that this article sets out to illuminate while the analysis of the sources of his books allow us to understand better his work.